2017
DOI: 10.1007/s11044-017-9564-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual muscle contributions to ground reaction and to joint contact, ligament and bone forces during normal gait

Abstract: Recent developments in musculoskeletal modelling have enabled numerous studies to explore how individual muscles contribute to progression, support and mechanical loading during gait. However, the literature still lacks data on the contributions of musculo-tendon forces to several structures, making it difficult to determine the primary contributors. The aim of the present study was thus to provide a comprehensive investigation of individual muscle contributions to ground reaction (i.e. 3D ground reaction forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…To check if the results were realistic or not a pseudo-validation using EMG data was used (Supplementary material 5). EMG results revealed no remarkable difference between the three CP trajectory models yet, the PCP model demonstrated a slightly better concordance with EMG data for rectus femoris and vasti muscle that are two main contributors to the first peak contact force (Moissenet et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…To check if the results were realistic or not a pseudo-validation using EMG data was used (Supplementary material 5). EMG results revealed no remarkable difference between the three CP trajectory models yet, the PCP model demonstrated a slightly better concordance with EMG data for rectus femoris and vasti muscle that are two main contributors to the first peak contact force (Moissenet et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…Firstly, modelling enables the investigation of cause–effect research questions that are otherwise impractical or impossible to directly assess [ 31 ]. For example, using an in silico approach, it is possible to assess the relationship between muscle force and joint loading during dynamic tasks such as walking [ 73 , 85 , 86 ]. Additionally, musculoskeletal modelling can overcome some limitations of cadaveric approaches, whereby interactions between muscle forces and whole-body skeletal dynamics can be accounted for [ 64 ].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…7a). Prior work investigating the stance phase of walking and running have also identified these muscles as the primary contributors to hip contact loading 7,[56][57][58] . However, these studies have typically shown GMED to provide the greatest contribution to hip compressive loading, whereas our work suggest the GMAX is the dominant contributor.…”
Section: Contribution To Frontal Plane Net Joint Momentsmentioning
confidence: 99%